The effect of the Mahatma Gandhi National Rural Employment Guarantee Act on the size of outstanding debts in rural India - Patwardhan, Sharvari; Tasciotti, Luca (Informa UK Limited, 2023)
MGNREGA was introduced in India in 2005 with the aim to improve the livelihood of rural Indian households. In 2012-13, around 156 million rural Indian households had an outstanding personal debt; 85% of the amount of credit being disbursed was given to those households in the bottom income decile for ‘non-business’ related purposes. This paper uses nationally representative household data from the NSS EUS collected in 2004-05 and 2009-10 to look at the impact MGNREGA has had on the rural households’ ability to repay outstanding debt. Results suggests that MGNREGA reduced the size of the outstanding debts for vulnerable households.